b-1=3b+6

Simple and best practice solution for b-1=3b+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-1=3b+6 equation:


Simplifying
b + -1 = 3b + 6

Reorder the terms:
-1 + b = 3b + 6

Reorder the terms:
-1 + b = 6 + 3b

Solving
-1 + b = 6 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-1 + b + -3b = 6 + 3b + -3b

Combine like terms: b + -3b = -2b
-1 + -2b = 6 + 3b + -3b

Combine like terms: 3b + -3b = 0
-1 + -2b = 6 + 0
-1 + -2b = 6

Add '1' to each side of the equation.
-1 + 1 + -2b = 6 + 1

Combine like terms: -1 + 1 = 0
0 + -2b = 6 + 1
-2b = 6 + 1

Combine like terms: 6 + 1 = 7
-2b = 7

Divide each side by '-2'.
b = -3.5

Simplifying
b = -3.5

See similar equations:

| -3x^3+8x^2-7x-1= | | 5x+5y=210 | | -9(2.5a+6.5)=22.5 | | a+6a+b+2b= | | 5x+19=61-2x | | 5x-4=4-x | | 8x^3+5x^3+7= | | y=8-0.4x | | 6x+21=13x+56 | | 7x+13=10x-5 | | 2000000x^4=80000 | | 372=2L+176 | | (8+4)x^3+8= | | 2(x-12)=3(x+5) | | 7s+5=26 | | -7(4.5v-3.5)=27.5-5.5v | | 372=2L+88 | | x^4=.04 | | 3+4(2x-3)=7 | | 5+3(2x-7)=5+6x-21 | | 24a-48=18a-36 | | 8x^3+4x^3+8= | | y=1.03 | | -4x-10=4(5x-4) | | 5xy-3b=11 | | 4-9x=y | | f(5)=10 | | 10x-2=-4x+10 | | D-6pie=pie | | 6x+12=(-12) | | 7-4(d-30)=23 | | -6s+8.5+5.5s=24.5 |

Equations solver categories